Design and operation of pilot plant for CO2 capture from IGCC flue gases by combined cryogenic and hydrate method - Surovtseva, Daria; Amin, Robert; Barifcani, Ahmed (Institute of Chemical Engineers (IchemE), Elsevier B.V., 2011)
This project is a trial conducted under contract with CO2CRC, Australia of a new CO2 capture technology that can be applied to integrated gasification combined cycle power plants and other industrial gasification facilities. The technology is based on combination of two low temperature processes, namely cryogenic condensation and the formation of hydrates, to remove CO2 from the gas stream. The first stage of this technology is condensation at −55 °C where CO2 concentration is expected to be reduced by up to 75 mol%. Remaining CO2 is captured in the form of solid hydrate at about 1 °C reducing CO2 concentration down to 7 mol% using hydrate promoters. This integrated cryogenic condensation and CO2 hydrate capture technology hold promise for greater reduction of CO2 emissions at lower cost and energy demand. Overall, the process produced gas with a hydrogen content better than 90 mol%. The concentrated CO2 stream was produced with 95–97 mol% purity in liquid form at high pressure and is available for re-use or sequestration. The enhancement of carbon dioxide hydrate formation and separation in the presence of new hydrate promoter is also discussed. A laboratory scale flow system for the continuous production of condensed CO2 and carbon dioxide hydrates is also described and operational details are identified.